The role of hyperthermic intraperitoneal chemotherapy (HIPEC) and isolated perfusion (ILP) interventions in sarcoma. Issue 5 (28th October 2014) - Colombo, Chiara; Baratti, Dario; Kusamura, Shigeki; Deraco, Marcello; Gronchi, Alessandro
Abstract : Locally advanced sarcomas in the extremity and in the retroperitoneum/abdominal cavity (peritoneal sarcomatosis, PS) can be managed administering chemotherapy locally using isolated limb perfusion (ILP) and hyperthermic intraperitoneal chemotherapy (HIPEC), respectively. In this review, the authors discuss the pros and cons of the use of these locoregional therapies in locally advanced soft tissue sarcoma, with a view to establishing their role in the multidisciplinary approach to these difficult diseases. J. Surg. Oncol. 2015 111:570–579 . © 2014 Wiley Periodicals, Inc.